2020
DOI: 10.1016/j.ijnss.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on nursing competence and training needs of dementia caregivers in long-term care institutions

Abstract: Objective It is aimed to investigate the nursing competence and corresponding influence factors of dementia caregivers in long-term care institutions of Tianjin and identify the training needs of caregivers. Methods In the cross-section survey of this study, 246 dementia caregivers were selected from 6 long-term care institutions in Tianjin as objects of study through convenient sampling. Results The scores for nursing competence of dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…Also, more than half of them residing at rural areas. These results were in accordance with Wang et al [20] in china whose study entitled as "Analysis on nursing competence and training needs of Alzheimer's caregivers in long-term care institutions" and revealed that 81% of the studied participants were married. Also, 63.1% of them residing at rural areas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, more than half of them residing at rural areas. These results were in accordance with Wang et al [20] in china whose study entitled as "Analysis on nursing competence and training needs of Alzheimer's caregivers in long-term care institutions" and revealed that 81% of the studied participants were married. Also, 63.1% of them residing at rural areas.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding to the total competence scores of formal caregivers regarding Alzheimer's disease.The findings of the current study revealed that more than half of the studied formal caregivers had higher competence regarding Alzheimer's disease. These results were Agree with the study performed by Wang et al [20], who stated that 56% of the studied participants had higher level of competence about care of Alzheimer patients. Concerning association between total knowledge and total attitude of formal caregivers regarding Alzheimer's diseases, the present study revealed that there were high statistically significant relation between total knowledge and total attitude at p value =0.005.…”
Section: Discussionsupporting
confidence: 84%
“…We found correlations between our participants' self‐assessed competence in nursing care with their age, work experience in dementia care and work experience in their current department. Wang et al (2020) also found that nursing competence of dementia nursing staff was positively associated with their work experience and educational level. In contrast, we detected a significant negative correlation between age and communication skills.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, the educational levels of disabled older adults were relatively low, such as primary school, middle school and technical secondary school levels, which was consistent with the results of the investigation conducted by Yongyang Yan et al 42 Due to knowledge limitations, disabled older adults had shortcomings such as a poor ability to study and comprehend new information. 43 Only a few disabled older adults had an undergraduate degree or higher, and most had attained only a middle school and technical secondary education. Thus, this population of older adults with low educational levels may need more telenursing-based long-term care to overcome their limitations.…”
Section: Discussionmentioning
confidence: 99%